The knowledge management as means dialectical for transformation in the school curriculum areas (Revista Electrónica REDINE, 2018)
In the new model of knowledge society, two essential elements, which are technology and education, which require management to more organizations by teachers to capitalize efficiently and effectively acquired knowledge of its members, are configured. In this sense, knowledge management must be understood as an instance of administration by which they are obtained, they deploy and use a variety of basic resources to support the development of knowledge in the field of education, specifically in the transformation of the curriculum of the educational system Venezuela, as must tackle to develop through the dialectic methodological knowledge that achieve a culture in relation to the curricular context. Therefore, this essay is to generate a reflection on the importance of knowledge management and processes to curriculum changes according to the needs presented in the areas of school participation purpose.
Keywords: knowledge management; dialectic; curriculum